Pertimbangan Hakim dalam Memutus Tindak Pidana Pembobolan Bank melalui ATM - Ida Ayu Gede Kristina Dewi; I Nyoman Gede Sugiartha; Ida Ayu Putu Widiati (Warmadewa Press, 2020)
Nowadays, advances in technology and information, criminal acts also often occur, automatic teller machines (ATMs) in the banking world are a form of Bank Customer Service that uses machines or can be said as well as electronic devices. Service is an important factor in attracting the attention of customers. Because of this technological sophistication as we know cyber crime, crime is a new form of contemporary crime that has been in the spotlight worldwide. Internet users here become victims because of crime through this electronic system by utilizing and seeing their virtual. In this research, there are at least two problems of violating the automatic cash register (ATM) account theft account: And (2) how is the judge's consideration in determining the crime of bank robbery through an ATM. The research method used is information retrieval using a normative approach based on legal sources, study of literature in studying the legal materials of the legislation as a process to find the rule of law, legal source collection techniques used in this research are records and documentation. Based on research it can be started that the criminal sanctions regulation against account robbery criminal acts. Through the Automatic teller Machine (ATM) in the Criminal Code law contained in Article 362 of the Criminal Code, in the ITE Law the theft is contained in Article 30 paragraph (1), Article 30 paragraph (3), Article 32 paragraph (2), Article 32 paragraph (3 ), Article 36. And there is an addition to Law Number 3 of 2011 concerning the transfer of theft funds contained in Article 81, Article 83 paragraph (1), Article 83 paragraph (2), decision number: 688 / PID. B / 2012 / PN. The judge ruled the case that the defendant was firmly proven legally and convincingly guilty of committing a crime against the law of buying, renting, exchanging, accepting as a promise, accepting as a gift or by accepting as a gift or in the hope of getting a profit selling, saving, exchanging, mortgaging, transported, stored or hidden items.